Detecting optic nerve head swelling on ultrasound and optical coherence tomography in children and young people: an observational study. Issue 3 (21st June 2017) - Dahlmann-Noor, Annegret Hella; Adams, Gillian W; Daniel, Moritz Claudius; Davis, Alison; Hancox, Joanne; Hingorani, Melanie; Ibanez, Patricia; McPhee, Becky; Patel, Himanshu; Restori, Marie; Roberts, Clare; Theodorou, Maria; et al.
Abstract : Background: Following high-profile cases, referrals for evaluation of 'suspicious optic discs' to eye clinics in the UK have sharply increased, asking ophthalmologists to reliably distinguish between true and pseudopapilloedema. Optic nerve sheath dilatation (ONSD) on ocular ultrasound (US) is considered a reliable sign of true papilloedema, but this test is not widely available. Recently, anterior bowing of Bruch's membrane (BM) and increased retinal nerve fibre layer thickness on optical coherence tomography (OCT) have emerged as indicators of intracranial hypertension, and OCT is widely available. We aimed to evaluate safety and efficacy of the diagnostic workup in our service, with particular emphasis of diagnostic reliability of US and OCT. Methods: Retrospective service evaluation/cohort study of children and young people younger than 16 years investigated for 'suspicious discs' over a 7-month period in 2016 at a single eye care provider in London, UK. 61 children and young people underwent clinical assessment, US scan and OCT. Results: Of 61 cases, 3 had intracranial pathology. At presentation, only one had ONSD on US and anterior bowing of BM on OCT. Increased nerve fibre layer thickness in at least one of three relevant sectors was observed in two cases. All three cases of intracranial pathology, however, had significant points in their presenting or medical history. Conclusion: Ophthalmologists and optometrists must not rely on funduscopy and ocular imaging when assessing a child for possible intracranial disease; history and basic neurological assessment are critical in the diagnostic workup.